An AutoCad-based subdivision - Mansor, Shattri; Thangam, J. R. (1989)
In recent years, software design to support computer aided design and drafting (CADD) operations has become popular. One commercial software package in this regard is AutoCad, from Autodesk Inc. An interactive subdivision design program developed based on an AutoCAD software (release 10) is described in this paper. The program was developed on the IBM PS/2 and is menu driven. It can be used for the design of traditional lot and street subdivisoins as well as for the design of planned unit developments. One can use the program to design subdivisions, modify subdivision, check subdivisions or prepare subdivision data for drafting and layout. The uniqueness of the program is its refreshing interface with the user and its flexibility increating and manipulating designs. It involves customization of AutoCAD for subdivision design requirements. System menus were modified to make often-needed commands more accessible. AutoCAD's internal programming language, AutoLISP, was used to create commands for performing calculations and for producing entities. Raw field data can be processed using land surveying software (written in BASIC) and interfaced with AutoCAD via DXF file.